Effect of Dimensions of Service Quality Satisfaction and Customer Loyalty of Islamic Bank in the Perspective of Islam in Palopo - Suhardi M. Anwar; Goso - (Journal of Education and Vocational Research, 2016)
This paper aims to analyze the quality of service using five dimensions that is tangible empathy, Reliability, Responsiveness, and Assurance. Where the first tangible dimension using attribute consists of the location, appearance of staff, office facilities are up-to-date, the cleanliness of the office, and exterior offices. The second dimension empathy that use attributes greet customers by name, an apology for the error service, understand customer needs, personal attention, and operational time. The dimensions of the third namely reliability that use service attributes as promised, timeliness of services, verification requests, and sincerity helped. The fourth dimension is the responsiveness attributes staff's willingness to help, the notification time of service, speed of service, readiness to serve. Then dimension the latter is the dimension of assurance that use attributes confidence in the ability of staff, courtesy staff, security transactions, and staff in still customer confidence. This research tested using SEM analysis, quality of service significant positive effect directly on customer satisfaction, means the better quality of service perceived by the customer, the higher the satisfaction of using services provided by the Islamic Bank in Palopo. Conversely, if the lower the quality of the service perceived by the customer, diminishing also their satisfaction to use the service provided by the Islamic Bank in the City of Palopo . Thus it can be conclusion that states that the quality of service in the perspective of Islam have a significant effect on customer satisfaction Islamic Bank in Palopo acceptable.